To Measure the Level of Depression Anxiety and Stress Using a Dass-21-Based Questionnaire on the Students of Shri Guru Ram Rai University, India - Naaz, Alisha; Anjum, Afsha; Gowami, Ujjwal; Kala, Kanishk (Indian Journal of Pharmacy Practice)
Objectives: The goal of this study is to evaluate the levels of depression, anxiety, and stress in university students by utilizing the Depression, Anxiety, and Stress Scale (DASS) and comparing the scores between male and female students. Materials and Methods: A total of 450 students were included in the study, with 411 providing consent to participate. The DASS-21 scale was used to collect data, and the study was conducted at the Shri Guru Ram Rai University in Patel Nagar, Dehradun, Uttrakhand, India. To present the data, univariate and bivariate tables, along with the chi-square test were used, and an independent t-test was employed to compare the DASS mean scores between male and female students. Results: The results showed that the mean scores for depression, anxiety, and stress were 5.39 ± 5.54, 5.53 ± 5.62, and 5.74 ± 5.05, respectively, with anxiety being the most prevalent among the students. Males generally had higher depression scores, whereas females exhibited greater anxiety and stress scores. Conclusion: It is essential to prioritize the mental health of students, given the increasing prevalence of depression, anxiety, and stress among university students, which can significantly impact their daily activities.
Keywords: DASS-21; Depression; Anxiety; University Students; Dehradun